The Influence of Product Innovation and Product Quality on Consumer Purchase Interest in PT. Alfasindo Metal in Jakarta - Priehadi Dhasa Eka (Jurnal Ad'ministrare, 2019)
This study aims to determine the effect of product innovation and product quality on consumer buying interest at PT. Alfasindo Metal in Jakarta. The method used was explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study Product Innovation significantly influence consumer interest by 40.8%, the hypothesis test obtained significance 0,000 <0.05. Product quality has a significant effect on consumer buying interest by 41.5%, hypothesis testing obtained significance of 0,000 <0.05. Product innovation and product quality simultaneously have a significant effect on consumer buying interest of 51.2%, the hypothesis test obtained a significance of 0,000 <0.05.